Exploring the potential of a standardized test in physiotherapy: making emotion, embodiment, and therapeutic alliance count for women with chronic pelvic pain - Boge-Olsnes, Cathrine Maria; Risør, Mette Bech; Øberg, Gunn Kristin (Frontiers in Psychology, 2023)
Introduction There has been an increased use of standardized measurements in health care meant to provide objective information to enhance the quality and effectivity of care. Patient performance tests are based on standardized predefined criteria with a limited focus. When facing multifaceted health conditions, information expanding the predefined criteria in a standardized test may be required to understand the patient’s complex symptoms. Relying on test information based on measurements according to functional biology, one risks missing information communicated by the sensitive and expressive body of the individual patient. The aim of this article is to investigate how body, self and illness perception is constituted as a co-construction between a physiotherapist and a patient with complex symptoms, expanding the use of a standard physiotherapy test. Methods This qualitative study is based on video-recordings and in-depth interviews of seven women with the complex health condition chronic pelvic pain. The video recordings consist of the patients performing the Standard Mensendieck test pre- and post-treatment with Norwegian psychomotor physiotherapy. The interviews are based on the patients` and the physiotherapists` conversations while watching and elaborating on these video recordings. Empirical data is analyzed within the theoretical perspectives of phenomenology and enactive theory, especially focusing on the concepts of embodiment and intersubjectivity. Results Taking an embodied approach, considering the body as expressive, communicative, and vulnerable to the environment and context, the results show that through bodily expressions the patients experienced the test situation as demanding, thus providing information beyond what the test was intended to measure. Additionally, when administering a standardized test, the interaction between the therapist and the patient had an impact on the results. Sensitive attention towards the patients bodily expressive emotions as a vital part of the interaction, reinforced therapeutic alliance by ensuring the integrity and autonomy of the patient. Discussion Mutual communication, gave new insights regarding the patients’ complex symptoms and reinforced their belief in themselves and their recovery processes. Applying the patient’s expertise on herself and her life together with the professional expertise may make health care an interdependent practice where sensemaking is a co-construction of meaning between the patient and the health personnel.